2017
DOI: 10.1007/s13524-017-0613-z
|View full text |Cite
|
Sign up to set email alerts
|

Children of Migrants: The Cumulative Impact of Parental Migration on Children’s Education and Health Outcomes in China

Abstract: Since the end of 1990s, approximately 160 million Chinese rural workers migrated to cities for work. Because of restrictions on migrant access to local health and education systems, many rural children are left behind in home villages to grow up without parental care. This article examines how exposure to cumulative parental migration affects children's health and education outcomes. Using the Rural-Urban Migration Survey in China (RUMiC) data, we measure the share of children's lifetime during which parents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
91
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 36 publications
0
91
1
Order By: Relevance
“…The survey was purposely designed to differentiate among urban families, rural families, and rural-urban migrant families. The research topics include migrant children's education, health and the extent to which they assimilate into city communities [68] [113]. CFPS (China Family Panel Survey) is a nationally representative longitudinal survey launched in 2010 by Peking University.…”
Section: Quantitative Datamentioning
confidence: 99%
“…The survey was purposely designed to differentiate among urban families, rural families, and rural-urban migrant families. The research topics include migrant children's education, health and the extent to which they assimilate into city communities [68] [113]. CFPS (China Family Panel Survey) is a nationally representative longitudinal survey launched in 2010 by Peking University.…”
Section: Quantitative Datamentioning
confidence: 99%
“…() found that paternal migration had significant and positive impacts on the academic performance of left‐behind children. Conversely, Meng and Yamauchi () and Zhao et al. () found that paternal migration had significantly negative effects on the academic performance of left‐behind children.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Bai et al (2018) and Chen et al (2009) found that paternal migration had significant and positive impacts on the academic performance of left-behind children. Conversely, Meng and Yamauchi (2017) and Zhao et al (2014) found that paternal migration had significantly negative effects on the academic performance of left-behind children. There also exist studies that found no significant effect of paternal migration on left-behind children's education (Li et al, 2017).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…However, the effect of the absence of only one parent is insignificant. Meng and Yamauchi (2015) find a sizable adverse impact of exposure to parental migration on children's educational as well as health outcomes. Biavaschi, Giulietti, and Zimmermann (2015) find that parental migration negatively affects children's educational attainment, but this negative effect is in part compensated for by the presence of an older sibling, especially an older sister.…”
Section: Introductionmentioning
confidence: 99%